Draft Tenth Five Year Plan 2002-2007 and Annual Plan 2002-2003 Volume I Thiruvanantpuram - Planning Commission (Planning Commission, 2002)
The draft state plan for the Tenth Five Year Plan (2002-07) has been prepared as a Reform Plan to remove the weaknesses in policies, finances, institutions, management and methods of work and the rigidities that have become entrenched in the system. It is essential to reform the public sphere so that its responsibilities are performed with utmost economy and efficiency for the benefit of the people. It is only through fundamental reforms that the public sphere will get back its capacity t© promote development, growth and employment, which are urgently needed. The draft has been prepared after wide consultations and on the lines broadly approved by the full Planning Board and the State Government.
State Planning Board Thiruvananthapuram Government of Kerala